Uncovering the Anticancer Mechanisms of Chinese Herbal Medicine Formulas: Therapeutic Alternatives for Liver Cancer - Chen, Feiyu; Zhong, Zhangfeng; Tan, Hor Yue; Guo, Wei; Zhang, Cheng; Tan, Chi-wing; Li, Sha; Wang, Ning; Feng, Yibin (Frontiers in Pharmacology, 2020)
The influential roles of Chinese herbal medicine formulas in various diseases are well known. Beyond its 2000-year history, herbal formula is appreciated for remarkable efficacy in lots of cases, which warrants a prominent position in public healthcare worldwide, especially in East Asian countries. Liver cancer is the second most fatal cancer across the world. Recent studies have extensively investigated the chemical profiles and pharmacological effects of Chinese herbal medicine formulas on liver cancer. Either through tracking volunteer patients or design-ing experimental researches, multiple herbal formulas have implicated benefits in the manage-ment of liver cancer. However, multi-component of each formula imposes restrictions on clini-cal practice and global recognition. Therefore, understanding in depth the mode of action of Chinese herbal medicine formulas may offer sufficient evidence for their clinical use. This re-view highlighted the chemical characteristics and molecular mechanisms of actions of Chinese herbal medicine formulas and summarized the correlated findings on the potential use in liver cancer treatment. At last, the present progresses of Chinese herbal medicine formulas in the perspective of clinical trials were discussed.